Chest pain CT in the emergency department: Watch out for the myocardium. (2018) - Higashigaito, Kai; Hinzpeter, Ricarda; Baumueller, Stephan; Benz, David; Manka, Robert; Keller, Dagmar I.; Alkadhi, Hatem; Morsbach, Fabian
Highlights: Hypodense myocardium (HM) can be observed often in chest pain CT examinations of patients presenting to the emergency department with chest pain. There is benefit when the myocardium is also analyzed for the presence of HM, even when the heart and coronary arteries were not specifically asked-for. Sensitivity, specificity, PPV and NPV for the detection of acute myocardial infarction by assessing HM was 52%, 100%, 100% and 95% respectively. Assessment of hypodense myocardium may increase the diagnostic confidence in ambiguous coronary findings in chest pain CT. Abstract: Rationale and Objectives: To evaluate the frequency and relevance of hypodense myocardium (HM) encountered in patients undergoing chest-pain CT in the emergency department (ED). Material and Methods: In this IRB-approved retrospective study, ECG-gated chest-pain CT examinations of 300 consecutive patients (mean age 60 ± 17 years) presenting with acute chest-pain to our ED were evaluated. Once ST-segment elevation infarction was excluded, chest-pain CT including the coronary arteries (rule-out acute coronary syndrome (ACS), pulmonary embolism (PE) and acute aortic syndrome (AAS): chest-pain CTcoronary, n = 121) or not including the coronary arteries was performed (rule-out PE and AAS: chest-pain CTw/o coronary, n = 179). Each myocardial segment was assessed for the presence of HM; attenuation was measured and compared to normal myocardium. Results: HM was identified in 27/300 patients (9%): 12/179 in chest-pain CTw/o coronary (7%) and 15/121 in chest-pain CTcoronary (12%). Mean attenuation of HM (40 ± 17 HU) was significantly lower than that of healthy myocardium (103 ± 18 HU, p < 0.001), with a mean difference of 61 ± 19 HU. In 15/27 patients (55.6%) with HM, the final diagnosis was acute MI, and in the remaining 12/27 patients (44.4%) previous MI was found in the patients' history. Chest-pain CTw/o coronary identified HM in 10/15 patients (66.6%) with a final diagnosis of acute MI. Conclusion: HM indicating acute MI are often encountered in chest pain CT in the ED, also in chest-pain CTw/o coronary when MI is not suspected. This indicates that the myocardium should always be analyzed for hypodense regions even when MI not suspected.